The Issue in Assessing Listening: What Listening Aspect May Be Problematic Assessed Trough the Utilization of Technology - Rohaniyah, Jaftiyatur; Nasrullah, Nasrullah (Universitas Nurul Jadid, 2021)
Assessing listening is the process of assessing the spoken text through the auditory insight. It requires the ability to recognize the spoken input with the auditory capacity and the knowledge of spoken language. The task and the activities are served in six listening types (reactive, intensive, selective, responsive, extensive and interactive listening) and the indicative answer is encoded by particular listening type focus on. While technology as vehicle to assess the learners’ listening skill, that by using the technology much more spoken input are established by native-speaker and teachers’ own record is used any. This study uses document analysis from the available previous studies to analyzing, evaluating and answering the problem which is encountered by student’s listening and either or not technology used in assessing listening can help them to improve their listening ability. An overview of some researches provide that student get challenge to comprehend the native spoken input delivery such as, an accent, the length of speech, long spoken passage and linguistic feature. The authentic dialogue provides less density and length of the information than the dialogue created in the textbook, that the information incorporated in the machine/technology less improve the students’ listening comprehension. It lacks to assess in the selective listening type that the task focus on taking the important information from the spoken text.